Penurunan Chemical Oxygen Demand (COD) Dan Fosfat (PO4-P) Limbah Laundry Menggunakan EM4 dan Mikroalga Spirulina sp - Kristin Ari Fitria; indah nurhayati; Joko Sutrisno (Jurnal Sains & Teknologi Lingkungan, 2023)
Laundry waste containing COD and PO4-P levels exceeds the quality standard so that it is released directly into the water body due to eutrophication. One technology to reduce COD and PO4-P uses symbiosis of Spirulina sp and EM4 microalgae. The purpose of this study was to examine the EM4 survey (0%, 5%, and 10%), aeration and residence time of 3 days, 6 days and 9 days for pH, COD and PO4-P in waste treatment using microbial symbiosis Spirulina sp and EM4 . Microalgae culture Spirulina sp using microalgae seedlings from Biological Laboratotrum University PGRI Adi Buana Surabaya, and culture carried out for 35 days to obtain a chlorophyll a concentration of 4.1 mg/L. EM4 before use was activated by fermentation for 7 days. Waste treatment is carried out with a laboratory-scale batch system using a 5 L volume glass reactor. The results showed EM4 concentration, aeration and residence time evaluation of the reduction in COD and PO4-P. PH during the study was stable around 8.1 - 8.3, the highest COD and PO4-P reduction in the reactor with the addition of 5% EM4 with aeration on the 3rd day with a final COD concentration of 283.5 mg/L with a decrease of 81,75%, and a final PO4-P concentration of 11.25 m /L with a reduction of 48.15%.